النخبة الإصلاحية في الجزائر: المرجعيات، الأعلام والامتدادات - بن نية، فاطمة Bin Niah, Fatemah (جامعة الأمير عبد القادر للعلوم الإسلامية - كلية أصول الدين, 2021)
يشكل البحث في تاريخ النخب وآليات تشكلها ومختلف تمظهراتها الاجتماعية والسياسية، موضوعاً ذا أهمية قصوى في العلوم الاجتماعية، إنه موضوع يمكننا من استبيان العلاقة التبادلية بين الحراك الاجتماعي ودور الأفراد والجماعات في هذا الحراك وتأثرهم به في الوقت نفسه. وانطلاقا من هذه العلاقة تحاول هذه الدراسة البحث في تاريخ النخبة الإصلاحية في الجزائر، كجماعة ذات انسجام نسبي تزاوج في نشاطها بين الجانبين الفكري والسياسي، وعلاقتها بالحركة الوطنية وبالحراك السياسي والاجتماعي للجزائر قبل وبعد الاستقلال، مع إضاءة للمرجعيات الفكرية والأصول الاجتماعية لهذه النخبة وأبرز أعلامها، وتأثيراتها الاجتماعية وتدخل ذلك التأثير مع الجانب السياسي الذي موضع الحركة الإصلاحية ككل في موقع حرج بين السلطة الاستعمارية ومختلفة تيارات الحركة الوطنية كممثلين لنخبة سياسية في طور التكوين بدورها.
Research in the history of the elites, the mechanisms that shape them and their various social and political manifestations is a subject of utmost importance in social sciences. It is a subject that allows us to explore the reciprocal relationship between the social movement and the role of individuals and groups in this movement as well as its influence on them. On the basis of this relationship, this intervention attempts to discuss the history of the reformist elite in Algeria as a group with a relative harmony that acted both on intellectual and political sides, and its relationship with the national movement and the political and social movement of Algeria before and after independence by highlighting the intellectual references, the social origins of this elite, its great figures, and its social effects in addition to the overlap of this influence with the political side so that it put the reform movement as a whole in a critical position between the colonial authority and the various currents of the national movement as representatives of a political elite in the process of formation.
Keywords: تاريخ الجزائر -- الحركة الإصلاحية -- النخبة الإصلاحية -- الإصلاح السياسي -- الإصلاح الاجتماعي -- الإصلاحيين الجزائريين